Sosialisasi Bahaya Seks Bebas Di Kalangan Remaja Sebagai Upaya Promotif Dan Preventif Di SMA Negeri 2 Tomohon (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2026)
Risky sexual behavior among adolescents is an increasingly concerning public health issue, particularly due to the lack of comprehensive sexual education in school and family environments. This community service activity aimed to improve the knowledge, awareness, and preventive attitudes of students at SMA Negeri 2 Tomohon regarding the dangers of free sex and the importance of maintaining reproductive health. The method used was educational socialization through interactive lectures, demonstrations, and open discussions involving 60 students as participants. Evaluation was conducted using pre-test and post-test instruments to measure improvements in participants' knowledge. The results showed a significant increase in knowledge, with the average pre-test score of 52.3 increasing to 80.7 in the post-test (a 54.3% improvement). A total of 91.7% of participants reached the good knowledge category after the activity, compared to only 18.3% before the activity. Participants also demonstrated more positive and critical attitudes toward the risks of free association. This activity affirms that interactive education-based socialization on reproductive health is effective in improving adolescent understanding. It is recommended that schools integrate reproductive health content regularly in counseling guidance programs to strengthen the sustainability of this activity's impact.